FORMATION OF PROFESSIONAL COMPETENCE OF A FUTURE COMPUTER SCIENCE TEACHER IN TEACHING THE SUBJECT OF INFORMATION SECURITY: The article is devoted to the consideration of the issues of designing and creating a methodological system for preparing future teachers to ensure the information security of students. (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
The article is devoted to the consideration of the issues of designing and creating a methodological system for preparing future teachers to ensure the information security of students. The formation of competencies of future computer science teachers in the field of information security will be more effective if the developed and implemented model of the competence formation methodology includes normative-target, methodological, content-organizational and evaluation. In our study, the design and development of a methodological system is based on the provisions of competence-based, modular, personality-oriented, activity-based and system approaches, as well as the concept of informatization of education. The analysis of the relationship of structural components made it possible to determine the systemic role of the goal, which determines the content of training, the choice of methods, means and forms of training that ensure its achievement. The presented model reflects the structural and functional components of the methodological system, in which its components are goals, content, methods, means, forms, learning outcomes in the form of meaningful content of the structural components of the training of future teachers.
Keywords: education, educational process, information security, training of computer science teachers, competence in the field of information security, methodological model.